Detection of Epithelial Cell Adhesion Molecule in Feline Normal and Tumor Cell Lines and Tissues With Selected Commercial Anti-human EpCAM Antibodies - Heyward, Christa Y.; Dong, Lynn; Shakhzadyan, Hayk; Wan, Christopher; Stokol, Tracy (Frontiers in Veterinary Science, 2021)
Epithelial cell adhesion molecule (EpCAM) is a transmembrane protein expressed at intercellular junctions in epithelial cells. As an epithelial biomarker, it used for immunologic-based capture of epithelial-derived circulating tumor cells (CTCs) in human patients with different carcinomas. EpCAM expression has not been described in normal or neoplastic epithelial tissues in cats. Our goal was to find a commercial antibody that recognizes surface EpCAM expression for CTC detection. We tested two anti-human EpCAM antibodies, designated for use with flow cytometry, for detection of surface EpCAM expression on feline cell lines derived from normal mammary and renal epithelia and mammary and oropharyngeal squamous cell carcinomas in cats. Only one of the antibodies, a goat polyclonal antibody, labeled normal and neoplastic feline mammary epithelial cells and oropharyngeal squamous cell carcinoma cells; no labeling was observed for normal feline kidney epithelial cells. At low dilution, this antibody immunohistochemically stained the intercellular junctions of normal pancreatic, intestinal and mammary epithelium, as well as neoplastic mammary epithelium in feline tissues; however, oral mucosa, skin and an oropharyngeal squamous cell carcinoma showed no positive immunostaining. The antibody only weakly bound feline squamous cell carcinoma cell lines under static adhesion. Our results indicate that EpCAM is expressed in specific epithelia in cats but is variably expressed in feline mammary tumors and oropharyngeal squamous cell carcinoma. A higher avidity cross-reactive or feline-specific antibody will be required to further investigate EpCAM expression in normal and neoplastic feline tissue or for detecting CTCs in the blood of tumor-bearing cats.